A novel differential protection scheme for HVDC transmission lines. (January 2018) - Zheng, Junchao; Wen, Minghao; Chen, Yu; Shao, Xinan
Highlights: A novel differential protection scheme for HVDC transmission lines is proposed. The application of ETPTL solve the calculation problem of voltage distribution. The capacitive current is calculated by integrating the linear distributed voltage. Abstract: Based on the compensation of the distributed capacitive current, a novel differential protection scheme for HVDC transmission lines was proposed in this study. According to the analysis, after voltage and current signals at both sides of the line are processed by the same low-pass filter the cut-off frequency of which is low enough, then the voltage distribution along the line can be regarded as linear distribution. The distributed capacitive current can be calculated by integrating the linear distributed voltage. After removing this current, the new differential criterion can be implemented. A ±800 kV HVDC transmission system was built in EMTDC to test the performance of the new protection. Comprehensive test studies show that the proposed method not only can detect internal faults correctly and quickly, but also can respond to internal faults with high ground resistance.